2004
DOI: 10.1177/0363546504263945
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up of Osteochondral Plug Transfers in a Goat Model

Abstract: Autogenous transplantation of osteochondral plugs is possible with integration of subchondral bone and preservation of chondral viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
102
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 35 publications
2
102
0
1
Order By: Relevance
“…Full integration has been reported in long-term experiments (Petersen et al 2008), whereas others reported a cleft between the recipient articular cartilage and osteochondral plugs in goats and human (Lane et al 2004;Horas et al 2003). Our study suggests that these results may reflect a difference in the total content of collagen in the implants, which is important for the interface shear strains.…”
Section: Discussionsupporting
confidence: 65%
“…Full integration has been reported in long-term experiments (Petersen et al 2008), whereas others reported a cleft between the recipient articular cartilage and osteochondral plugs in goats and human (Lane et al 2004;Horas et al 2003). Our study suggests that these results may reflect a difference in the total content of collagen in the implants, which is important for the interface shear strains.…”
Section: Discussionsupporting
confidence: 65%
“…However, the integration of donor and recipient hyaline cartilage can be impaired because of diff erent mechanical properties and thickness. 79,147,241 Other possible disadvantages are the limited availability of graft s and the risk of donor site morbidity. 147,327 Furthermore, the use of a medial malleolar osteotomy to approach the lesion has been associated with a worse outcome, i.e., local osteoarthritis and higher morbidity 143 A randomized controlled trial with 2 years of follow-up comparing OATS with debridement (with or without microfracture) showed similar results among the methods.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, due to its nature of a higher-level vertebrate and non-pet status when compared to dogs, goats play a significant role in the orthopaedics field as a feasible model for orthotopic applications. In addition, goats not only have metabolic and bone remodelling rates similar to that of humans but also a comparable sequence of events in bone graft incorporation and healing capacities (Pearce et al, 2007), which explains the fact that this model has been frequently used in studies of bone formation and regeneration (Kruyt et al, 2004;Li et al, 2006;Zhu et al, 2006), biocompatibility (Mendes et al, 2001) and osteochondral regeneration (Lane et al, 2004;Niederauer et al, 2000).…”
Section: Introductionmentioning
confidence: 95%